The Novel as Cultural Geography: Elizabeth Gaskell’s North and South - Knežević, Borislav (2011)
The article examines the work of cartography in the 1854/5 Gaskell novel North and South, which has long been considered an example of the genre of the industrial novel dealing with capital/labour relations. The novel is analyzed as a complex exercise in the mapping of the national space, which involves creation of the map stretching from the global to the domestic. An argument is made that in the mid-19th century the English novel took upon itself to take part in the articulation of knowledge about society that the novelists felt was necessary at the time when society was rapidly changing and new discourses on social relations were needed. The article claims that the spatiality in Gaskell’s novel needs to be read in relation to three historical coordinates: the topical imperative of the condition of England debate, the work of imagining the nation that characterizes the novel as a genre, and the ability of the novel as a genre to narrativize the mediations between the private and the public: in case of North and South, there is the clear example of mediating conventions of domestic fiction and social-issue topical literature.
Projekt MZOS
ENG